ENVELOPMENT: A METHODOLOGICAL APPROACH IN STRUCTURATION OF URBAN DIALECTICS - Atun, Resmiye A. (Open House Int, 2016)
The visualisation and the level of abstraction of complicated organic relations within an urban setting still remains a major problem with regard to urban discipline. This paper captures the dialectic relation within the urban network, in which the interaction between the spatial process of becoming and the temporal state of being is fundamental. 'Envelopment' is developed from and based upon Giddens' structuration theory. It enables visualisation of 'relations' and, as problem-setting matrices, allows the fundamentals of the urban network to be itemised within forms of relationships: modalities. Deleuze and Guattari's philosophy of deterriorialisation is also adopted into urban studies to support further investigations in respect of decoding and Translating 'modalities' as fundamentals in achieving continuous reproduction of Envelopment-as a topological space. Generally, topological space is defined in terms of processes and relations, Vocabularies are accepted as essences of urban dialog embodied in the system, needs to be visualised and meanings to be assigned according to their role and position in the system. In envelopment, system will be considered as macro-scale, multi-scalar topology, where all other modes of relations (amongst people, space and time) can be elaborated. The language game of Wittgenstein, as a metaphoric tool allows us to explore and group the modes of relations as vocabularies; set of modalities, enabling dialog upon their role and position in the system. Although the approach of Envelopment can be used as a tool, in enabling the representation of the equilibrium of state and process characteristics of system; it also helps as a tool in enabling the representation of macroscopic space-time scale; enabling representation of urban development and enabling representation of change in urban narrative. The various implementation of the Envelopment will be represented as a final discussion of the paper.
Keywords: Urban Assemblage; Envelopment; Structuration; Modalities; Topological Space